A formal evaluation of The Ottawa Hospital Pain Clinic orientation session: A quality improvement project - Patricia A. Poulin; Louise Bell; Danielle Rice; Yaadwinder Shergill; Sarah Fitzgerald; Rosemee Cantave; Renée Gauthier; Rose Robbins; Cristin Kargus; Susan Ward (Taylor & Francis Group, 2023)
ABSTRACTBackground Chronic pain affects approximately one in every five Canadians and has a substantial impact on psychological well-being, relationships, ability to attend work or school, and overall functioning.The Ottawa Hospital Pain Clinic introduced orientation sessions, with the aim of providing new patients with pain education to help prepare patients for engagement with multimodal pain management strategies. This report summarizes the results of a formative evaluation of the orientation session at The Ottawa Hospital Pain Clinic to determine whether patients perceived the orientation session as beneficial.Methods Interviews were conducted, transcribed, and then thematically analyzed to understand patients' perspectives on the orientation session. Coding was done by two team members using the constant comparison analyses method with key ideas, concepts, and patterns identified and compared to identify similarities.Results Between September 6 and October 18, 2019, 18 patients attended an orientation session and 12 consented to participation and completed telephone interviews. The six themes identified included (1) feeling of community, (2) participants feeling heard by providers, (3) appreciation of the holistic approach, (4) availability of community resources, (5) barriers to access, and (6) discordant feelings of preparedness for the physician appointment.Conclusion Results from this evaluation indicate that the orientation session offered at The Ottawa Hospital Pain Clinic improves chronic pain literacy, reduces feeling of isolation, and instills hope. As such, it appears to be a valuable component of pain clinic programs.